DMA Based Physical Water Loss Management and Infrastructure Leakage Index Analysis in Asian Side of Istanbul - Mehmet Melih Koşucu (Doğal Afetler ve Çevre Dergisi)
Physical water losses are usually caused by pipe breaks in water distribution networks and leaks at pipe joints and storage facilities. Managing these losses is critical to not only improve the operating conditions of infrastructure, but also to deliver economic, environmental and societal benefits. This study presents how water losses were analysed and managed in a District Metered Area (DMA) located on the Asian side of Istanbul. Minimum night flow rate (MNF), leakage flow rate and infrastructure leakage index (ILI) analyses were used to reduce and manage the physical losses frequently seen in water distribution networks. For the years 2023 and 2024, flow data obtained from SCADA measurements were used to analyze the minimum flow values occurring at night and to estimate the level of water losses. By reducing the average inlet pressure of the DMA from 65 m to 60 m together with active leakage control (acoustic listening and pipe repair), the water loss rate was reduced from 29.8 % to 18.9 %. In addition, the infrastructure leakage index value was reduced from 8.7 to 5.6 with the improvement efforts. Thus, through DMA-based water loss analysis and management, it has been possible to operate the studied water distribution system more efficiently. In this study, it is emphasised that DMA-based pressure and flow monitoring, active leakage control and pressure management techniques are important tools to reduce water losses, especially in metropolitan areas. The findings are guiding for sustainable water management that can contribute to policies to reduce water losses in our country.